Fuel ethanol price drivers in the Atlantic basin: Brazil & the U.S. traders perspectives - Portinho Júnior, José (2010)
Because the opportunity for exporting ethanol fuel is very new, agribusiness needs literature for training managers and strategists. This paper aims to describe the mechanism of price formation of ethanol in Brazil and the United States of America. I have divided the mechanism into smaller pieces and evaluated each of the variables that impact the pricing, cost of production of ethanol from cane sugar, cost of logistics and dehydration on the Caribbean cost of corn ethanol and did some analysis of scenarios of pricing of key variables and could organize this knowledge into a graph that contains in upper axis the price hydrous ethanol FOB mill in Brazil and in the bottom axis the price of corn in Chicago whose crossing straight in the dollar rate and the price of natural gas, supply in the Y axis the price of the anhydrous ethanol in New York harbor, enabling an easy view of the possibilities of the export window. The methodology allows you to assume different scenarios of supply, demand and prices and then build alternative trade strategies.